Citizen Science Discovery of a Recurrently Active Jupiter-Family Comet: (551023) 2012 UQ192 - DeSpain, Jarod A.; Chandler, Colin Orion; Oldroyd, William J.; Hsieh, Henry H.; Trujillo, Chadwick A.; Burris, William A.; Kueny, Jay K.; Farrell, Kennedy A.; Mendoza Magbanua, Mark Jesus; Sedaghat, Nima; Sheppard, Scott S.; Mazzucato, Michele T.; et al. (Research notes of the AAS, 2023)
We have discovered evidence of cometary activity originating from (551023) 2012 UQ 192 (alternately designated 2019 SN 40 ), which we dynamically classify as a Jupiter Family Comet (JFC). JFCs have eccentric Jupiter-crossing orbits and originate in the Kuiper Belt. Analysis of these objects can provide vital information about minor planets in the outer solar system, such as the distribution of volatiles within the solar system. Activity on 2012 UQ 192 was first recognized by volunteers on our NASA Partner Citizen Science project Active Asteroids . Through our own examination of archival image data, we found a total of ∼30 images presenting strong evidence of activity near perihelion during two separate orbits. 2012 UQ 192 is notable as we found it to be recurrently active. When 2012 UQ 192 approaches its perihelion passage in 2027 September, we predict it will reactivate and will be a prime subject for follow-up observations.